Reverse Submammary Adipofascial Perforator Flap: Preliminary Results of a Dual-plane, Acellular Dermal Matrix–free, Direct-to-implant Hybrid Reconstruction - Diego Ribuffo, MD, PhD; Marco Marcasciano, MD, PhD; Federico Lo Torto, MD, PhD; Jacopo Nanni, MD; Luca Patanè, MD; Lorenzo Calabrese, MD; Davide Marino, MD; Donato Casella, MD, PhD; Manfredi Greco, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Single-stage direct-to-implant (DTI) reconstruction, particularly the prepectoral technique, has become prominent due to its reliable outcomes and shorter operative time. This approach spares the pectoralis major muscle, reducing postoperative pain and morbidity, and ensuring quicker recovery. However, limitations such as patient comorbidities and tumor characteristics can limit feasibility, leading to complications and high reconstructive failure rates. In such cases, switching to autologous or 2-stage approaches becomes necessary. This study introduced an innovative acellular dermal matrix–free dual-plane DTI hybrid reconstruction using a reverse submammary adipofascial perforator flap for small-volume breasts. Methods:. A prospective noncontrolled cohort study was conducted from January to April 2024, enrolling 10 breast cancer patients eligible for DTI reconstruction. Data collected included preoperative clinical characteristics, intraoperative surgical data, and postoperative outcomes, including complications and patient satisfaction measured using BREAST-Q version 2.0. Breast aesthetics was also evaluated by 12 independent observers at minimum 3 months follow-up. Results:. The surgical technique involved a dual-plane pocket with a reverse submammary adipofascial perforator flap, harvested from the inframammary fold, anchored to the pectoralis major muscle for inferolateral pole coverage of the breast implant. Results showed 1 major complication requiring surgical revision and 1 minor skin flap necrosis managed conservatively. All patients reported good satisfaction with their reconstruction results, supported by positive aesthetic evaluations from observers. Conclusions:. This acellular dermal matrix–free, dual-plane DTI hybrid technique seems safe and effective for small-volume breasts. It offers a viable alternative for selected cases, warranting further investigation with larger cohorts and longer follow-ups.